2011
DOI: 10.1007/s00464-011-1680-7
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcomes in palliative gastrointestinal stenting: a Norwegian multicenter study

Abstract: BackgroundThe clinical effect of stent treatment has been evaluated by mainly physicians; only a limited number of prospective studies have used patient-reported outcomes for this purpose. The aim of this work was to study the clinical effect of self-expanding metal stents in treatment of malignant gastrointestinal obstructions, as evaluated by patient-reported outcomes, and compare the rating of the treatment effect by patients and physicians.MethodsBetween November 2006 and April 2008, 273 patients treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 28 publications
1
9
0
1
Order By: Relevance
“…Though some reports suggested that patients with advanced malignant biliary obstruction, who were beyond chemotherapy, should not be offered PTBD; [11] other studies have shown improvement in pruritus and other high-bilirubin symptoms post procedure due to drop in bilirubin levels. [14,26] In one study, the patients' quality of life was observed to improve after PTBD despite that serum bilirubin level did not drop down to normal; where mean serum bilirubin level before PTBD was 19.85 mg/dL and after the procedure at 1 month it became 6.02 mg/dL. [27] Unfortunately, due to the retrospective nature of our study, we could not evaluate for patients' quality of life, pre-and post-procedure.…”
Section: Discussionmentioning
confidence: 91%
“…Though some reports suggested that patients with advanced malignant biliary obstruction, who were beyond chemotherapy, should not be offered PTBD; [11] other studies have shown improvement in pruritus and other high-bilirubin symptoms post procedure due to drop in bilirubin levels. [14,26] In one study, the patients' quality of life was observed to improve after PTBD despite that serum bilirubin level did not drop down to normal; where mean serum bilirubin level before PTBD was 19.85 mg/dL and after the procedure at 1 month it became 6.02 mg/dL. [27] Unfortunately, due to the retrospective nature of our study, we could not evaluate for patients' quality of life, pre-and post-procedure.…”
Section: Discussionmentioning
confidence: 91%
“…1). The reduced focus on anxiety may be related to the adaptation to the disease after proper information and that reduced reporting of itchiness may be explained by procedures like stenting [22]. However, both these dimensions remained in the PACADI score since they obviously are important in the early phases of the disease, which may be the phases of largest interest when considering current and future therapeutic options.…”
Section: Discussionmentioning
confidence: 99%
“…The study found significant improvement in emotional, cognitive, and global health ( P < 0.01) in the patients who survived to follow-up, improvement in pruritus and jaundice ( P < 0.01), and improved anorexia, diarrhea, and sleep ( P < 0.01). A study of endoscopic stents in 40 patients with malignant biliary obstruction 9 found statistically significant improvements after two weeks in EORTC QLQ-C30 global health function (from 30 to 48; P = 0.003) and in symptoms, including pain and pruritus. A third study examined 109 patients (94% with advanced disease) and found a statistically significant improvement in pruritus at one month (2.26–0.75; P < 0.01), using a visual analogue scale, but a significant decrease in QOL (101.3–94.7; P < 0.01), using the Functional Assessment of Cancer Therapy-Hepatobiliary instrument.…”
Section: Resultsmentioning
confidence: 99%